The Role of the Philosophy of Science in Critical Thinking and Ethical Decision-Making: A Systematic Literature Review - Nerma Jelestari; Elni Septi; Sunayah Sunayah; Yeni Astria; Dewi Angraini (Yayasan Sembilan Pemuda Indonesia, 2026)
The philosophy of science plays a vital role in shaping scientific inquiry, guiding the way knowledge is constructed, validated, and applied across disciplines. However, there remains a lack of comprehensive understanding regarding its relevance and application in the context of contemporary education and technology. Therefore, this study aims to systematically review recent research trends and conceptual developments related to the philosophy of science within the 21st-century academic landscape. This study employed a Systematic Literature Review (SLR) approach using publications indexed in Scopus from 2015 to 2025. A total of 85 articles were analyzed through bibliometric mapping and qualitative synthesis to identify emerging patterns and dominant themes. The results reveal three major synthesized themes: (1) the integration of the philosophy of science in educational practices to strengthen epistemological awareness; (2) its role in navigating the ethical and epistemic challenges of digital technology; and (3) its contribution to fostering critical and reflective scientific thinking. The novelty of this study lies in highlighting the evolving interface between philosophy of science and technological transformation in education. Practically, the findings provide a conceptual framework for integrating philosophical reflection into scientific and technological curricula. This study contributes to the advancement of science and technology by offering a holistic understanding of how philosophical foundations can support the development of responsible, innovative, and reflective scientific practices.